Dynamic Game Problems of Approach for Fractional-Order Equations - Eydelman, S. D.; Chikrii, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We propose a general method for the solution of game problems of approach for dynamic systems with Volterra evolution. This method is based on the method of decision functions and uses the apparatus of the theory of set-valued mappings. Game problems for systems with Riemann–Liouville fractional derivatives and regularized Dzhrbashyan–Nersesyan derivatives (fractal games) are studied in more detail on the basis of matrix Mittag-Leffler functions introduced in this paper.